2010
DOI: 10.1186/1479-5876-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in genes of the Angiotensin and Serotonin systems and risk of hypertrophic cardiomyopathy: AT1R as a potential modifier

Abstract: BackgroundAngiotensin and serotonin have been identified as inducers of cardiac hypertrophy. DNA polymorphisms at the genes encoding components of the angiotensin and serotonin systems have been associated with the risk of developing cardiovascular diseases, including left ventricular hypertrophy (LVH).MethodsWe genotyped five polymorphisms of the AGT, ACE, AT1R, 5-HT2A, and 5-HTT genes in 245 patients with Hypertrophic Cardiomyopathy (HCM; 205 without an identified sarcomeric gene mutation), in 145 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In humans, mutations in MYBPC3 typically exhibit low and age‐related penetrance in heterozygotes. A few modifying genes and their proteins have been identified that contribute to the penetrance of these mutations, including the angiotensin‐converting‐enzyme gene and the gene that encodes for the angiotensin1‐receptor . These and other “modifying” genes, suggested by the incomplete penetrance and phenotypic heterogeneity, have not been identified in cats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mutations in MYBPC3 typically exhibit low and age‐related penetrance in heterozygotes. A few modifying genes and their proteins have been identified that contribute to the penetrance of these mutations, including the angiotensin‐converting‐enzyme gene and the gene that encodes for the angiotensin1‐receptor . These and other “modifying” genes, suggested by the incomplete penetrance and phenotypic heterogeneity, have not been identified in cats.…”
mentioning
confidence: 99%
“…A few modifying genes and their proteins have been identified that contribute to the penetrance of these mutations, including the angiotensin-converting-enzyme gene and the gene that encodes for the angiotensin1-receptor. 16 These and other "modifying" genes, suggested by the incomplete penetrance and phenotypic heterogeneity, have not been identified in cats. Furthermore, no other major HCM causative mutations in other feline breeds have been identified.…”
mentioning
confidence: 99%
“…A total of seventeen studies were included in our review [1], [13], [20], [21], [23], [25], [26], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44]. For ACE I/D polymorphism, a total of 31 prospective trials surveyed the polymorphism of ACE I/D.…”
Section: Resultsmentioning
confidence: 99%
“…13 Abnormalities in the renin-angiotensin system, namely specific polymorphisms in the angiotensin genes, have been suggested as potential candidate mechanisms capable to explain coexisting myocardial and vascular hypertrophy and fibrosis in HCM patients. 14 Recently, Boonyasirinant et al reported an increased aortic stiffness in patients with HCM, above all in those with myocardial fibrosis. 15 All these data imply that HCM, apart from being a cardiac disease, may also affect the vascular system, with structural changes of the arterial wall, rearrangement, and remodeling of its three-dimensional architecture limiting maximal vasodilator capacity.…”
Section: Discussionmentioning
confidence: 98%